2012 39th Annual International Symposium on Computer Architecture (ISCA) 2012
DOI: 10.1109/isca.2012.6237024
|View full text |Cite
|
Sign up to set email alerts
|

A first-order mechanistic model for architectural vulnerability factor

Abstract: Soft error reliability has become a first-order design criterion for modern microprocessors. Architectural Vulnerability Factor (AVF) modeling is often used to capture the probability that a radiation-induced fault in a hardware structure will manifest as an error at the program output. AVF estimation requires detailed microarchitectural simulations which are time-consuming and typically present aggregate metrics. Moreover, it requires a large number of simulations to derive insight into the impact of microarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Nops and wrong-path instructions are assumed to be non-ACE. Table 2 shows the configurations of the big out-of-order and the small in-order core types, as well as the bit counts per entry in each structure (taken from Nair et al [22]). Note that we assume the same cache hierarchy for the small and big cores; however, in Section 10 where we focus on L1 cache vulnerability, we will vary the cache size of the small core to study the sensitivity to the cache hierarchy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nops and wrong-path instructions are assumed to be non-ACE. Table 2 shows the configurations of the big out-of-order and the small in-order core types, as well as the bit counts per entry in each structure (taken from Nair et al [22]). Note that we assume the same cache hierarchy for the small and big cores; however, in Section 10 where we focus on L1 cache vulnerability, we will vary the cache size of the small core to study the sensitivity to the cache hierarchy.…”
Section: Methodsmentioning
confidence: 99%
“…Sridharan and Kaeli [42] propose to split AVF into PVF (program vulnerability factor) and HVF (hardware vulnerability factor), which can be determined independently. Other prior work models AVF through regression on performance counters [43], [44], or through analytical mechanistic modeling [22]. Nair et al [45] develop a methodology for creating AVF-stressing benchmarks, providing a processor AVF upper bound.…”
Section: Monitoring Modeling and Improving Reliabilitymentioning
confidence: 99%
“…[42] [23] Arch. injection [9] [41] [30] ACE analysis [26] [27] Probabilistic models [20] In this paper, we propose a comprehensive architecturelevel fault injection framework for early reliability estimation of x86 microprocessors. The proposed framework:…”
Section: Techniquesmentioning
confidence: 99%
“…Prior research has shown that AVF varies at instruction granularities within applications [15]. AVF sensitivity to microarchitectural resource sizes was studied in [16]. These studies demonstrate that AVF varies from workload to workload and for a given workload, it varies from one CCM to another.…”
Section: Introductionmentioning
confidence: 99%